Evaluación del proceso de Biosorción de cadmio mediante el uso de biomasas de citrus X Sinensis (naranja) y Selenicereus Megalanthus (Pitahaya amarilla - Pazmiño Solórzano, Silvia Belén (2021)
The presence of cadmium in the environment can become an environmental problem that must be treated efficiently to avoid health risks, new treatment methods must be effective in elimination and economical, research aims to evaluate the cadmium biosorption process through the use of Citrus X sinensis (orange) and Selenicereus megalanthus (yellow pitahaya), using for its evaluation the completely random design with 8 treatments and 3 repetitions, we worked with 1.4 g of biomass and 100 mg/L with cadmium solutions (5, 10 and 15 mg/L),the pH was adjusted (4.5), the tests were carried out at room temperature at (200 rpm) in contact time intervals (1, 3 and 5 hours). The tests were analyzed by the atomic adsorption spectrometry (EAA) method, the model revealed 99.95% variability in cadmium absorption, in the concentration of 5 mg/L of Cd the best result was obtained with values of (0.49; 0.84 and 0.86 mg /L) of orange peel and yellow pitahaya with values of (0,19; 0.31 and 0.24 mg/L), the biosorption of cadmium in relation to the time in each biosorbent occurred during 1 hour, in the percentage of removal the orange peel presented 90.2% and yellow pitahaya 96.4%. It was concluded that the yellow pitahaya reported greater ion retention capacity in the contact time of one hour, using a concentration of 5 mg / L of Cd. Keywords: Orange, yellow pitahaya, biosorption